Three-dimensional study on the interaction between a container ship and freak waves in beam sea - Jiaqian Wang; Hao Qin; Zhe Hu; Lin Mu (International Journal of Naval Architecture and Ocean Engineering, 2023)
Freak wave occurs unexpectedly in the ocean with an extreme wave crest and focused wave energy, resulting in many marine accidents. The interaction between a container ship and freak waves in beam sea is studied in this paper to better understand the influence of freak waves on ships. A three-dimensional in-house solver is developed and validated for the freak wave generation and the wave-ship interaction. Characteristics of the interaction process, motion responses of the ship and the green water loadings induced by the freak waves are obtained and analyzed. Comparisons are carried out to reveal the influences of the freak wave crest and sequence on the roll, heave and impact pressures. Relations between motion responses of the ship and the green water event are discussed. Influences of ship speeds on the wave-ship interaction are addressed.